Book Review: Abbink, Jon. 2017: A Decade of Ethiopia: Politics, Economy and Society 2004–2016. (April 2018) - Cochrane, Logan
Abbink, Jon. 2017: A Decade of Ethiopia: Politics, Economy and Society 2004–2016 . Leiden: Brill. 253 pp. 24.00. ISBN: 9789004345881.